Synchronizability and Synchronization Rate of AC Microgrids: A Topological Perspective - Yu, Chang; Xiao, Wenqian (IEEE transactions on network science and engineering, 2024)
When various distributed generation (DG) technologies are integrated into an islanded AC microgrid (MG), the system's heterogeneous characteristics make synchronizing all units within the network more challenging. From the perspective of complex networks, the capability of an islanded MG to achieve synchronization is closely associated with its physical topology. Consequently, a pressing need exists for a theoretical analysis of the network topology's influence on synchronizability in AC MGs. In this paper, we first develop a concise criterion for the synchronization condition of AC MGs and then introduce the definition of the synchronizability index, which measures the robustness of synchronization against disturbances such as voltage sags, sudden load changes, and component failures. Subsequently, we investigate the topology effect on synchronizability in islanded AC MGs for cases involving additional new connections or a unit node. Moreover, we provide an explicit expression of the general algorithm for computing the synchronization rate associated with topology parameters, such as the incidence matrix, weight matrix, and algebraic connectivity, among others, in the MG. The condition for the maximum synchronization rate is also explored. Finally, the accuracy of the theoretical results is validated through several test systems.